Teaching literacy to learners with dyslexia a multisensory approach - Kelly, Kathleen; Phillips, Sylvia (SAGE, 2022)
This bestselling text offers theoretical detail and depth alongside a programme of activities to implement in practice which can improve literacy levels and support children with dyslexia"--